Pentameroid brachiopod Karlsorus new genus from the upper Wenlock (Silurian) Slite Beds, Gotland, Sweden. (9th August 2017) - Jin, Jisuo; Holmer, Lars E.
Abstract: Karlsorus n. gen. is proposed in this study as a large, smooth-shelled pentameride brachiopod of the family Pentameridae, based on Pentamerus gothlandicus Lebedev, 1892, from the Wenlock (Silurian) Slite beds of Gotland, Sweden. This species is transferred from Pentamerus to the new genus because of the combination of a Pentamerus -like shell shape and the development of a brachiophorium through fusion of the outer hinge plates in the middle portion, like a dorso-ventrally inversed cruralium. The first appearance of brachiophorium in pentamerids is in the late Wenlock, known also in Brooksina, Pentamerifera, and other related pentamerid genera, marking a significant stage in morphological transformation of dorsal internal structures, as part of the Silurian pentameride diversification in both level-bottom and reefal depositional environments.